Construção e desconstrução do mito do quinto império na literatura colonial e pós-colonial portuguesa : O Branco da Motase de Rodrigues Júnior vs O Esplendor de Portugal de António Lobo Antunes - Agnès Levécot (Carnets)
The Fifth Empire myth sustained by the Estado Novo finds in Portuguese Colonial Literature a priviledged means of expression. Here the construction of the national myth is made up of concrete structures (railways, properties, etc...) whose realist description is enrichened by several universal myths such as the Creation, the Noble Savage, the Promised Land, the Sacred Legacy, the Universal Harmony. Nevertheless, in Rodrigues Junior’s novel there is some questioning of these myths that eventually lead to the fall of the imperialist ideology, a fall repeatedly metaphorized in the first part of A. Lobo Antunes’s works, particularly in O Esplendor de Portugal.